In Vivo siRNA Delivery Using JC Virus-like Particles Decreases the Expression of RANKL in Rats - Daniel B Hoffmann; Kai O Böker; Stefan Schneider; Ellen Eckermann-Felkl; Angelina Schuder; Marina Komrakova; Stephan Sehmisch; Jens Gruber (Elsevier, 2016)
Bone remodeling requires a precise balance between formation and resorption. This complex process involves numerous factors that orchestrate a multitude of biochemical events. Among these factors are hormones, growth factors, vitamins, cytokines, and, most notably, osteoprotegerin (OPG) and the receptor activator for nuclear factor-kappaB ligand (RANKL). Inflammatory cytokines play a major role in shifting the RANKL/OPG balance toward excessive RANKL, resulting in osteoclastogenesis, which in turn initiates bone resorption, which is frequently associated with osteoporosis. Rebalancing RANKL/OPG levels may be achieved through either upregulation of OPG or through transient silencing of RANKL by means of RNA interference. Here, we describe the utilization of a viral capsid-based delivery system for in vivo and in vitro RNAi using synthetic small interfering RNA (siRNA) molecules in rat osteoblasts. Polyoma JC virus-derived virus-like particles are capable of delivering siRNAs to target RANKL in osteoblast cells both in vitro and in a rat in vivo system. Expression levels were monitored using quantitative real-time polymerase reaction and enzyme-linked immunosorbent assay after single and repeated injections over a 14-day period. Our data indicate that this is an efficient and safe route for in vivo delivery of gene modulatory tools to study important molecular factors in a rat osteoporosis model.